2018
DOI: 10.4103/ijpsym.ijpsym_512_17
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Quality of Life in Cancer Patients: Medical and Psychological Intervention

Abstract: Background: Cancer pervades many dimensions of an individual's life – demanding a holistic treatment approach. However, studies with combined medical and psychological interventions (MPIs) are sparse. High-level stress and poor quality of life (QoL) can hinder patients' prognosis. The study thus aimed to analyze the impact of combined medical and psychological (psychoeducation, relaxation technique–guided imagery, and cognitive therapy) interventions on stress and QoL of cancer patients – head and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 37 publications
1
27
2
5
Order By: Relevance
“…However, we observed that an increase in the QoL index was significantly higher in the PNI group than in the controls. The combination of psychoeducation, relaxation technique-guided imagery, and cognitive therapy significantly diminishes stress and increases QoL in patients with head and neck, breast, and lung cancers (Barre et al, 2018). This improvement could be associated with less severe clinical symptoms and a higher immune function since QoL was correlated negatively with duration of fever and positively with CD8+ T and CD4+ T cell count, as well as with IgM and IgA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed that an increase in the QoL index was significantly higher in the PNI group than in the controls. The combination of psychoeducation, relaxation technique-guided imagery, and cognitive therapy significantly diminishes stress and increases QoL in patients with head and neck, breast, and lung cancers (Barre et al, 2018). This improvement could be associated with less severe clinical symptoms and a higher immune function since QoL was correlated negatively with duration of fever and positively with CD8+ T and CD4+ T cell count, as well as with IgM and IgA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…An important implication of the findings summarized above is that βAR blockade should reduce the levels of VEGF, IL-1β, and RANKL produced by osteoblasts (and presumably osteocytes) in response to sympathetic activation, and thus offer some level of protection against bone metastatic events. It is important to emphasize that, in addition to a number of social stressors, the diagnosis of cancer and its treatment have a significant impact on the stress level of patients [44,[224][225][226][227][228]. β-blockers are used for the treatment of multiple conditions, including congestive heart failure, hypertension, migraines, infantile hemangioma, and thyrotoxicosis [229].…”
Section: Treatment Strategies To Limit Metastatic Cancer Cell Engraftment Into the Skeletonmentioning
confidence: 99%
“…Psychosocial stress was associated with an increased incidence of colorectal, lung, head and neck, hepatobiliary, esophagus [ 11 ], prostate [ 12 ], bladder, rectal, stomach [ 13 ], and lymphoid or hematopoietic cancers [ 4 ] in some recent studies. Encouragingly, however, combined psychological interventions have a positive impact in cancer patients via decreasing stress and improving quality of life, and further improving prognosis [ 14 ].…”
Section: Chronic Stress and Cancermentioning
confidence: 99%